Characteristic Study Of Physiochemical Properties Of Hybrid Biofuel (Palm Oil And Alcohol Blend) For Compression Ignition Engine Application - Maidin, Mohammad Amiruddin Mohd. (Universiti Sains Malaysia, 2017)
Exponential growth of industrialization and motorization has led arising of petroleum and energy demand. This results in the search for a new form of energy to cater the depletion of fossil fuel and the environmental degradation condition. Straight vegetable oils is a renewable alternatives to diesel fuel at the same time provide a cleaner burning, but having high viscosity compared to diesel is undesirable for diesel engines. In this work, the physiochemical properties of diesel fuel, cajuput oil, refined palm oil and ethanol mixtures at various compositions were studied. Kinematic viscosity as a function of time, density and calorific value of these biofuel were studied to be compared to American Society for Testing and Materials Standard (ASTM D6751) to formulate a biofuel that could be as reliable as diesel fuel running in compression ignition engine. The results indicate that kinematic viscosity of biofuel decrease with an increase in temperature. Among all 24 samples, the best formulated biodiesel is 10% refined palm oil with 90% diesel (10RPO:90D), followed by 20% cajuput oil with 80% diesel (20MCO:80D) .While for biofuel, 60% cajuput oil with 40% refined palm oil (60MCO:40RPO) is the best formulated biofuel. The commercialization of this particular biodiesel and biofuel could result in the decrease reliance towards using diesel fuel solely for compression ignition engine. This finding contributes by proposing a new straight vegetable oil which is cajuput oil that has not yet being studied in term of its fuel capability to substitute conventional diesel fuel.